How do income support systems in the UK affect labour force participation? - Institute for Labour Market Policy Evaluation, Uppsala; Brewer, Mike (Uppsala, 2009)
"This paper reviews how income-support systems affect labour force participation in the UK. The UK’s approach to social insurance is “basic security”, with modest, typically flat-rate, benefits; insurance-based benefits are relatively unimportant. Compared with the EU, the UK has high employment rates, but a high proportion of non-workers say that they are not working through disability. In general, the low generosity of out-of-work benefits means that positive incentives to work exist for almost all benefit recipients, but weak work incentives exist for those receive Housing Benefit, and for primary earners in couples who have low earnings. Recent reforms to strengthen work incentives have altered the in-work tax credits, rather than the benefit system, and recent reforms to the out-of-work benefits have involved toughening and extending job-search requirements. The two main political parties seem to agree that future reforms will involve more conditionality, a greater use of the private sector, and a unification of the different labour market programmes."